RoGoPaG - Rossellini, Roberto; Godard, Jean-Luc; Pasolini, Pier Paolo; Gregoretti, Ugo; Bernardo, Mario; Delle Colli, Tonino; Rabier, Jean; Trasatti, Luciano; Schiaffino, Rosanna; Welles, Orson; Bory, Jean-Marc; Tognazzi, Ugo (Pier Paolo Pasolini - Volume 1, 2007)
Four short films by four celebrated directors. In Roberto Rossellini’s "Illibatezza (Chastity), an Italian air hostess (Maria Pia Schiaffino) in Bangkok is pursued by an American businessman (Bruce Balaban). In Pier Pasolini’s "La Ricotta", notions of religion and belief are explored as a biblical blockbuster is being filmed outside Rome. Jean-Luc Godard’s "Il Nuovo Mondo" (The New World) is a look at a post-nuclear explosion future. Finally, Ugo Gregoretti’s "Il Pollo Ruspante" (The Free-Range Chicken) is a satire on modern living. Pasolini’s contribution earned him a suspended prison sentence for blasphemy. [www.moviemail.com]